History of Development on Muslim Women’s Education Empowerment through Wasatiyyah Concept in Brunei Darussalam - Lilly Suzana Shamsu (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2018)
This article is an attempt to explore the application of Wasatiyyah in the education system in Brunei Darussalam. This research will be focusing on the advancement of Muslim women’s education since the Nation’s Policy of Education has been formulated. In such, Annual Education Report and related government official documents are to be analyzed as the main resource in this article. In brief, the methodology used is library research which will be presented in descriptive and narrative approach. As a result, the research found that it is certainly notable Wasatiyyah concept is part of the country education system. It is clear and noticeable with no restriction on gender to enroll in all schools. The opportunity to get an education is equally open to all children. Besides, the government is constantly offering and encouraging all adult Muslim women to engage in long life learning with providing them with adult education to enhance their skills and knowledge in numerous field.